Rituals for Climate Change A Crip Struggle for Ecojustice - Ortiz, Naomi (punctum books, 2023)
Disability justice and ecojustice are rarely considered together but are in constant conversation in our world. Rituals for Climate Change: A Crip Struggle for Ecojustice, combining poetry and the lyrical essay, doesn't contain just one point of view but encompasses dialectical perspectives which often exist in contradiction to each other. A disabled person is in need of plastic cups and concerned about the overwhelming plastic in our ecosystems. Ortiz expands on and complicates who is seen as an environmentalist and what being in relationship with the land can look like. This book is an offering to explore the spiritual question of how to witness. It serves as a companion to those also grappling with the difficult and often unanswerable questions posed by climate change in the borderlands. By exploring the ways body, mind, and cultures both clash with and long for ecojustice, Rituals for Climate Change offers an often-overlooked perspective on climate-grief, interdependence, and resilience. Disabled people know how to adapt to a world that is ever changing without considering them.